2017
DOI: 10.4103/ijpvm.ijpvm_338_16
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing activity of extracts and formulations of aloe vera, henna, adiantum capillus-veneris, and myrrh on mouse dermal fibroblast cells

Abstract: Background:Among the most important factors in wound healing pathways are transforming growth factor beta1 and vascular endothelial growth factor. Fibroblasts are the main cell in all phases wound closure. In this study, the extracts of plant materials such as Adiantum capillus-veneris, Commiphora molmol, Aloe vera, and henna and one mixture of them were used to treatment of normal mouse skin fibroblasts.Methods:Cytotoxic effects of each extract and their mixture were assessed on mouse skin fibroblasts cells u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…These relations demonstrate tissue repair-associated fibroblast migration and proliferation, and that ECM remodeling-related collagen synthesis in fibroblasts plays important roles during skin wound healing and regeneration [5,16]. Although many strategies have been devised to promote skin wound healing [17], they remain unsatisfactory, and thus control of skin cell proliferation, migration, and collagen synthesis appears to be a promising strategy for promoting skin wound healing and regeneration, Many plants and plant extracts have been used traditionally to treat diverse disorders [18], and the wound healing effects of many plant extracts have been investigated due to their minimal side effects and low manufacturing costs [1,19]. Furthermore, the development of herbal therapeutic materials that accelerate wound healing has recently drawn research attention.…”
Section: Introductionmentioning
confidence: 99%
“…These relations demonstrate tissue repair-associated fibroblast migration and proliferation, and that ECM remodeling-related collagen synthesis in fibroblasts plays important roles during skin wound healing and regeneration [5,16]. Although many strategies have been devised to promote skin wound healing [17], they remain unsatisfactory, and thus control of skin cell proliferation, migration, and collagen synthesis appears to be a promising strategy for promoting skin wound healing and regeneration, Many plants and plant extracts have been used traditionally to treat diverse disorders [18], and the wound healing effects of many plant extracts have been investigated due to their minimal side effects and low manufacturing costs [1,19]. Furthermore, the development of herbal therapeutic materials that accelerate wound healing has recently drawn research attention.…”
Section: Introductionmentioning
confidence: 99%
“…These steps can be characterized into four highly programmed phases such as hemostasis, inflammation, proliferation and remodeling [2,6,[12][13][14][15][16]. All phases of healing must occur in suitable sequence for successful healing as a natural phenomenon [6,12,13] but sometimes complex multifactorial process of wound healing can be delayed or failed by unwanted effects such as presence of free radicals [12,17] or microbial infections [5,12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, herbal extracts were found to induce significant proliferation and viability of human dermal fibroblasts at concentrations ranging from 5 to 25 µL/mL. mouse fibroblast cells in vitro (15).…”
Section: Discussionmentioning
confidence: 88%